The Constructive Role of Teacher Enthusiasm and Clarity in Reducing Chinese EFL Students’ Boredom - Song, Yang (Frontiers in Psychology, 2022)
With the rise of positive psychology, the role of teachers’ emotions and interpersonal communication skills have been recently highlighted in the literature. However, the preventive role of teacher enthusiasm and clarity in reducing EFL students’ boredom has not caught sufficient attention among L2 scholars. Against this gap, this article, first, presented the definitions, dimensions, and conceptualizations of teacher enthusiasm, clarity, and students' boredom. Next, theoretical and empirical backgrounds were provided to support the claim that enthusiasm and clarity of EFL teachers can stop students’ classroom boredom. Additionally, the study presented the implications and future directions of this line of research for different people such as EFL teachers, teacher trainers, and L2 scholars. The ideas can improve their awareness of teachers’ positive emotions, interpersonal skills, and their roles in L2 education.